Ambiguitas Putusan Mahkamah Konstitusi Republik Indonesia Dalam Perkara Nomor 91/PUU/MK-VXIII/2020 - alkahfi setiawan, sidi (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2022)
The Constitutional Court is a new institution in Indonesia that also handles dispute resolution on judicial review in Indonesia. This is related to the new order era, there was no official institution authorized to examine the formation of legislation. One form of testing the legislation is to examine the implementation of Law Number 11 of 2020 concerning Job Creation which uses the omnibus law system in the preparation of the legislation. Whereas in the legal system in Indonesia as regulated in Law Number 15 of 2019 concerning the Establishment of Legislation, it does not recognize the omnibus law system but rather on the codification of laws such as the Civil Code and Law Number 7 of 2017 concerning Elections. The emergence of this work copyright law cannot be separated from the many laws and regulations that apply in Indonesia which actually hinder investment. This over-regulation is caused by every institution and every problem, laws and regulations can be formed, which in the end actually creates a synchrony between the laws and regulations.